Pelatihan Pembuatan Media Pembelajaran untuk Meningkatkan Ecoliteracy Anak Usia Dini di PAUD Se-Kecamatan Kota Agung Timur, Kabupaten Tanggamus, Provinsi Lampung - Nopiana Nopiana; Nia Fatmawati (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
Environmental education from an early age is the key to forming a generation that cares about environmental sustainability. Early childhood has the ability to absorb positive values ​​effectively through concrete, visual, and fun learning. However, there are still many educators in PAUD who do not have the skills to design learning media that support the improvement of ecoliteracy. Therefore, this community service activity aims to provide training to PAUD teachers in Kota Agung Timur District, Tanggamus Regency, Lampung Province on how to create creative learning media based on the environment. The method of implementing the activity includes socialization, technical training in making media (such as posters, recycled story books, and teaching aids from used materials), and mentoring implementation in the classroom. The results of the activity showed an increase in teachers' understanding of the concept of ecoliteracy and skills in creating interesting and environmentally friendly learning media. In addition, teachers stated that the media produced was able to increase children's enthusiasm and awareness of the importance of protecting the environment. This activity is expected to be the first step in encouraging sustainable environmental education at the PAUD level.